2012
DOI: 10.1051/0004-6361/201219812
|View full text |Cite
|
Sign up to set email alerts
|

SDO AIA and EVE observations and modelling of solar flare loops

Abstract: We present imaging and spectroscopic observations of an isolated C1-class solar flare, obtained with the Atmospheric Imaging Assembly (AIA) and Extreme ultraviolet Variability Experiment (EVE) on the Solar Dynamics Observatory (SDO). We obtain excellent agreement between the peak flare temperatures estimated using the EVE spectra with those obtained from GOES and, most importantly, from the ratio of the 94 Å and 131 Å AIA channels, which are found to be dominated by Fe xviii and Fe xxi. These results confirm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…When the Fe xviii emission becomes dominant, we found good agreement between observations and theory (Petkaki et al 2012), suggesting that the AIA 94 Å calibration is correct, given that the atomic data we provided for Fe xviii should be reliable (Witthoeft et al 2006;Del Zanna 2006).…”
Section: Aia 94 åsupporting
confidence: 72%
See 1 more Smart Citation
“…When the Fe xviii emission becomes dominant, we found good agreement between observations and theory (Petkaki et al 2012), suggesting that the AIA 94 Å calibration is correct, given that the atomic data we provided for Fe xviii should be reliable (Witthoeft et al 2006;Del Zanna 2006).…”
Section: Aia 94 åsupporting
confidence: 72%
“…When flare-like emission is present, significant continuum and Fe xxi (formed around 10 MK) emission is present in the 131 Å band, with some contribution also from Fe xx and Fe xxiii (see Petkaki et al 2012;Del Zanna & Woods 2013 shows the total AIA count rates due to the Fe xii 186.8, 192.4, 193.5, and 195.1 Å lines, all observed by EIS. These count rates were obtained by converting the EIS calibrated radiances into AIA DN/s.…”
Section: Aia 131 åmentioning
confidence: 99%
“…These empirical adjustments do not have any justification when one considers in detail the underlying atomic data. For example, these adjustments modify the high-temperature peaks of the two bands, which are dominated by well-known lines from Fe xviii and Fe xxi (O'Dwyer et al 2010;Petkaki et al 2012), for which the atomic data are accurate.…”
Section: Aia Responsesmentioning
confidence: 99%
“…The first event was the GOES C1.2 flare on 2011 March 3, UT 19:24-19:44, which was thoroughly studied by Petkaki et al (2012) and who found that the 94 Å emission band was dominated by the Fe xviii line and the 131 Å band by the Fe xxi line, which correspond to the hot contributions. Therefore, to avoid overprocessing we have used the original AIA observations.…”
Section: Datamentioning
confidence: 99%
“…In the study of the dynamics of a small flare, Petkaki et al (2012) perform a similar temporal background subtraction selecting the value of the lowest total emission in the 94 Å and 131 Å channels. Figure 3 maps the background-subtracted 94 Å intensity along the five loops through time.…”
Section: Loop Identification and Definition Of The Inter-moss Regionmentioning
confidence: 99%